Public Health and Healthcare Reform in Russia - T. O. Tagaeva; L. K. Kazantseva (Мир новой экономики)
The article analyses the state of public health in modern Russia, the dynamics of demographic indicators, healthy life expectancy, primary and general morbidity, disability, mortality in infancy and working age. We also present comparisons using international statistics from the World Bank, the World Health Organization and the OECD. Further, we give the characteristic of the factors influencing public health in Russia. The article presents the results of Russian researchers of public health and their foreign colleagues, showing that most of the deaths and diseases of Russians are the result of an incorrect lifestyle. The most significant contribution to mortality and health deterioration has such phenomena as high blood pressure (which itself is a consequence of an unhealthy lifestyle), alcohol abuse, smoking and overweight. The most detailed attention we paid to the underfunding of the health care industry and the negative consequences of the process of its reform.